The role of cardiac ultrasound virtual simulation technology in the construction of clinical diagnostic reasoning of structural heart diseases - Qianyun Wang; Feifei Wang; Can jiang; Jun Guo (BMC Medical Education)
Abstract Background Clinical reasoning education is a very systematic and highly logical medical learning process, but the existing teaching models and methods often divide this process into several stages for separate training using a virtual reality (VR)simulator can simulate and reconstruct the cardiac anatomical structure, ultrasonic section operation, and color doppler ultrasound parameter measurement, then integrate it into a single disease or case. In this case, the students' operation skills,decision-making and communication skills were trained by cardiac physical examination, inquiry and interpretation of laboratory examination results. This study aims to investigate whether the application of virtual simulation technology in cardiac ultrasound learning can improve students' thinking ability in the diagnosis and treatment of structural heart diseases. Method This study involved fifty-nine undergraduate students studying clinical medicine in the fifth semester at Jinan University. We employed a simple randomization method for random grouping. Random numbers were generated in Excel based on the students' student IDs. Then the students were sorted and divided into the experimental group, which used virtual simulation teaching based on ultrasound, and the control group, which used traditional teaching method. Following the completion of theory teaching, operation demonstration, clinical skills practice and VR practice, students underwent an offline image assessment and online systematic test, which included cardiac ultrasound operation assessment and virtual simulation case assessment to evaluate their proficiency in clinical skills and analytical ability in clinical reasoning. Furthermore, the VR group was given a separate questionnaire to provide their feedback on the cardiac ultrasound virtual simulation education. Results There were no statistically significant differences between the two groups in the scores for offline image interpretation and patient inquiry in the virtual simulation case analysis (P > 0.05). The scores for physical examination in virtual simulation case analysis (P < 0.05), virtual simulation ultrasound manipulation(P < 0.05) and diagnosis in virtual simulation case analysis(P < 0.05) were higher in the VR group than in the control group, and the difference was statistically significant. The total score for all evaluation of teaching quality in the VR group was higher than in the control group (P < 0.05). Furthermore, the majorityof students in the VR group displayed satisfaction with course experience, learning effect, teaching evaluation, and overall evaluation. Conclusion This research demonstrates that cardiac ultrasound virtual simulation technology could improve students' thinking ability in diagnosing and treating of structural heart diseases. The virtual simulation technology not only could be used for technology imitation but also could leverage its characteristics to demonstrate the process of a certain disease from anatomy to pathophysiology and clinical signs from shallow to deep.